Discussion on "The Neoproterozoic glacial record in the Río de La Plata Craton: a critical reappraisal" - Pazos, Pablo Jose (2010)
Pecoits et al. assert that in the ‘latest compilations of the geology of Uruguay’  the Zanja del Tigre Formation is part of the Carapé Group and not the Lavalleja Group.  However, this disregards  the contemporaneous stratigraphic scheme of Sánchez Bettucci (1998), which includes the Zanja del Tigre Formation in the Lavalleja Group. This is the stratigraphic scheme followed by Pazos et al. (<st1:metricconverter productid="2008, in" w:st="on">2008, in</st1:metricconverter> press), Mallmann et al. (2007) and Basei et al. (2008). We further point out that the geochronological results presented by Mallmann et al. (2007) and Basei et al. (2008) were not available to us at the time of writing. However, we dispute the suggestion that the absence of detrital zircons younger than 1.8 Gyr from the Zanja del Tigre Formation necessarily demonstrates a Mesoproterozoic depositional age, significantly older than that of Lavalleja Group (Basei et al. 2008). Some units within undisputed Neoproterozoic sedimentary successions elsewhere in Uruguay and Argentina similarly lack Neoproterozoic detrital zircons (Gaucher et al. 2008). Detrital zircon data can only be used to place lower limits on sedimentation.